(untitled) (Journal of Population and Development, 2023)
This research paper examines the trends, patterns, and diversifications of overseas labour migration from Nepal to different countries worldwide. This study analyzes the changing trends of human resource migration from Nepal around the world. In the same way, it elucidates the causes of migration from Nepal. The study uses quantitative methods to analyze the data. Different census reports show a continuous flow of Nepalese workers, and military personnel abroad over the past 250 years. Due to relatively higher income levels in the Gulf States and Malaysia, the proportion of migrants going to India has drastically declined lately. A rapid migration of Nepalese to Gulf countries and other developed countries took place after 1990. The recent census data exhibit that the trend of migrating overseas to new destinations is increasing and it also reveals that the migrating tendency of males is about four times higher than that of females. Nepal, one of the world’s major remittance-receiving developing countries, has gained recognition in recent years for gaining foreign currency from its migrant workers. As a result, Nepal has undergone transformations in the fields of its culture, political ideology, and technology. Therefore, overseas migration has contributed to the socio-economic development of the nation.